2019
DOI: 10.1080/03075079.2019.1626364
|View full text |Cite
|
Sign up to set email alerts
|

Against the odds: an investigation into student persistence in UK higher education

Abstract: This article focuses on student persistence in Higher Education. It examines qualities that enable students to persist in their studies despite the challenges they face, and key factors interplaying with and affecting these qualities. This study utilised the explanatory mixed-methods approach. It comprised a faculty-wide survey which explained the relationships between and across variables. Focus group interviews explored significant predictors of students' persistence. Results from this study showed that, amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The high-performing students' verbal accounts revealed habits of reframing adversity and actively pursuing optimism as they made sense of their experience of digital learning. This finding aligns with a study of student persistence in UK higher education, which found that key drivers of students' perseverance are "personal optimism, academic engagement, and positive relationships" and that "successful student persistence tends to be a result of an intricate interaction between the student's personal factors and their environment" (Gabi & Sharpe, 2019). When teaching was suddenly and unexpectedly moved to the digital classroom the learning environment that teachers were able to create from their home-offices played a key role in the students' experience.…”
Section: Discussion and Reflectionsupporting
confidence: 86%
“…The high-performing students' verbal accounts revealed habits of reframing adversity and actively pursuing optimism as they made sense of their experience of digital learning. This finding aligns with a study of student persistence in UK higher education, which found that key drivers of students' perseverance are "personal optimism, academic engagement, and positive relationships" and that "successful student persistence tends to be a result of an intricate interaction between the student's personal factors and their environment" (Gabi & Sharpe, 2019). When teaching was suddenly and unexpectedly moved to the digital classroom the learning environment that teachers were able to create from their home-offices played a key role in the students' experience.…”
Section: Discussion and Reflectionsupporting
confidence: 86%
“…Offline learning environments foster a conducive atmosphere for maintaining motivation and concentration, enabling students to sustain their commitment to learning. Offline learners frequently exhibit self-motivation, driven by their overarching learning goals and aspirations to fulfill their educational objectives (Gabi & Sharpe, 2021;Xuereb, 2014). When faced with moments of boredom or distraction during offline learning, students proactively employ strategies to refocus their attention and reignite their motivation to continue learning.…”
Section: Discussionmentioning
confidence: 99%
“…Offline learning environments facilitate increased peer-to-peer interactions (Yen et al, 2018) and student-instructor interactions (Kite et al, 2020), which students leverage to seek help effectively when encountering learning difficulties. Engaging in communication and seeking assistance from peers not only enhances students' self-regulation skills (Alvi & Gillies, 2015;Dunn et al, 2014) but also expedites task completion through guidance from instructors (Gabi & Sharpe, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The study of engagement presents its beginnings in the workplace. However, it has recently begun to be analysed in higher education, sometimes as one of the variables that can influence the intention to persist the studies (Gabi & Sharpe, 2021;Kwon & Jung, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%